2020
DOI: 10.1186/s42501-020-00057-x
|View full text |Cite
|
Sign up to set email alerts
|

Asia–Gondwana connections indicated by Devonian fishes from Australia: palaeogeographic considerations

Abstract: Middle Palaeozoic vertebrate fossil occurrences are summarised for Australia, with reference to faunal connections between Asia and East Gondwana, as first indicated by fish distributions of Lower Devonian fossil sites. Major endemic groups discussed are pituriaspid (Australian) and galeaspid (Asian) agnathans, wuttagoonaspids (Australian) and antarctaspid (Antarctic, Australian, Asian) arthrodires, yunnanolepid and sinolepid antiarchs (South China, Indochina terrane, Australia), and early tetrapodomorphs (Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Janvier (2007; [54]) suggested that the ‘horizontal caudal lobe’ of osteostracans might be a modified anal fin. Galeaspids and pituriaspids appear to lack an anal fin [60, 61] but uncertainty is due to the poor preservation of their postcranial skeleton. In gnathostomes, the anal fin is not preserved usually in ‘placoderms’, probably due to its reduced size and the cartilaginous nature of the radials, but has been illustrated in some cases (e.g., arthrodires like Africanaspis and Dunkleosteus ) [62, 63]).…”
Section: Discussionmentioning
confidence: 99%
“…Janvier (2007; [54]) suggested that the ‘horizontal caudal lobe’ of osteostracans might be a modified anal fin. Galeaspids and pituriaspids appear to lack an anal fin [60, 61] but uncertainty is due to the poor preservation of their postcranial skeleton. In gnathostomes, the anal fin is not preserved usually in ‘placoderms’, probably due to its reduced size and the cartilaginous nature of the radials, but has been illustrated in some cases (e.g., arthrodires like Africanaspis and Dunkleosteus ) [62, 63]).…”
Section: Discussionmentioning
confidence: 99%
“…Weems (2004) questioned the validity of B. virginiensis. Since there is no consensus on the species level of Bothriolepis and Asterolepis, the former researchers only used the evidence of Antiarcha on the genus level to discuss the biostratigraphic significance (Lelievre and Goujet, 1986;Pan, 1981;Young et al, 2010;Young and Lu, 2020). To keep accuracy and consistency, here we choose the genus of Antiarcha to perform data visualization.…”
Section: Data Processing and Quality Controlmentioning
confidence: 99%
“…The genus then occurs later in Gondwana and Kazakhstan between the Givetian and Famennian (e.g. [62,71]). Until now, the occurrence of Bothriolepis in Euramerica was confined to the Upper Devonian, but has now been lowered to the middle Givetian with B. dairbhrensis sp.…”
Section: Stratigraphic Record Of the Genus Bothriolepismentioning
confidence: 99%